Rapidly vanishing lung pseudotumor in a patient with acute bilateral bronchopneumonia - Lazović, Biljana; Stajić, Zoran; Putniković, Biljana (Vojnosanitetski pregled, 2017)
Introduction. Rapidly vanishing lung pseudotumor (phantom tumor) refers to the transient well-demarcated accumulation of pleural fluid in the interlobar pulmonary fissures. Most frequently their appearance is associated with congestive heart failure, but also other disorders like hypoalbuminemia, renal insufficiency or pleuritis. Its rapid disappearance in response to the treatment of the underlying disorder is a classical feature of this clinical entity. Case report. A 47-year-old woman, chronic smoker with symptoms of shortness of breath, orthopnea, chills, cough, weakness and the temperature of 39.2°C was admitted to our hospital. A posteroanterior chest X-ray revealed cardiomegaly with the cardiothoracic ratio of > 0.5, blunting of both costophrenic angles and an adjacent 6 ´ 5 cm well-defined, rounded opacity in the right interlobar fissure. Transthoracic 2-dimensional echocardiography demonstrated left ventricular hyperthrophy with a systolic ejection fraction of 25% and moderate mitral regurgitation. The patient’s symptoms resolved rapidly after diuresis, and repeated chest X-ray four days later showed that the right lung opacity and pleural effusions had vanished. Conclusion. The presented case underlines the importance of the possibility of vanishing lung tumor in patients with left ventricular failure and a sharp oval lung mass on the chest X-ray. This is the way to avoid incorrect interpretation of this finding causing additional, unnecessary, costly or invasive imaging, interventions and drugs.   Key words: lung; radiography; diagnosis, differential; heart failure; bronchopneumonia.
Keywords: lung; vanishing tumor; acute bronchopneumonia; Heart Failure; Congestive; chest radiography; pseudotumor